The effects of awareness, knowledge and financial support on the success of young entrepreneurs in SME Tube Programs - Nur Zahidah, Kader Maideen (2024)
The thesis examines how awareness, knowledge, and financial support impact the success of young entrepreneurs in SME Tube Programs in Perak. The study aims to assess the influence of these factors on the effectiveness of SME Tube programs for young entrepreneurs. One hundred twenty-eight (128) respondents participated in the study, and data was collected through a questionnaire survey using random sampling methods. The results indicate that awareness and financial support significantly impact the success of young entrepreneurs in SME Tube Programs in Perak, with awareness being the most crucial predictor. This research seeks to provide insights into how improving awareness and financial support can enhance the success of young SME Tube entrepreneurs’ programs, and it offers valuable recommendations for policymakers and program designers committed to supporting young entrepreneurs